2017
DOI: 10.13080/z-a.2017.104.003
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of winter spelt cultivars to reduced tillage system and chemical plant protection

Abstract: A three-factor field experiment evaluated grain yield, yield components and some grain quality traits (Zeleny sedimentation value and the contents of protein, gluten, starch, carotene, lutein, zeaxanthin and amino acids) of eight winter spelt cultivars as influenced by the tillage system (conventional and reduced tillage) and chemical plant protection (application of two herbicides: Mustang 306 SE and Attribut 70 WG, a fungicide Alert 375 SC and a growth regulator Stabilan 750 SL). Plots without the use of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
5
16
0
Order By: Relevance
“…However, the date of harvesting did not significantly affect the K content in spelt grain. This was in accordance with the results of other authors [13,26] who noted a similar content of macronutrients in ripe spelt grain and green grain.…”
Section: Grainsupporting
confidence: 94%
See 2 more Smart Citations
“…However, the date of harvesting did not significantly affect the K content in spelt grain. This was in accordance with the results of other authors [13,26] who noted a similar content of macronutrients in ripe spelt grain and green grain.…”
Section: Grainsupporting
confidence: 94%
“…Furthermore, the present study confirmed the relationship indicated by Kraska et al [20] in their study, in which the content of the essential amino acids Lys and Met as well as that of the nonessential amino acid Ala was shown to be higher in green grain compared to the spelt grain harvested at the fully ripe stage. Andruszczak [26] also reported a similar amino acid composition in spelt grain. The highest Asp content was identified in bread with 12% addition of green spelt grain among all the bread samples evaluated (Table 6).…”
Section: Amino Acid Compositionmentioning
confidence: 76%
See 1 more Smart Citation
“…The revived interest in spelt can be attributed to the high nutritional value of its grain, which is rich in protein, macronutrients and micronutrients [38][39][40][41][42][43][44][45], resistance to fungal pathogens [18,[46][47][48][49][50][51], and higher adaptability to varied environments and simplified farming systems in comparison to bread wheat [52][53][54]. The milling quality of spelt grain has been recently investigated by Wiwart et al, Rapp et al,and Sobczyk et al [44,45,55].…”
Section: Discussionmentioning
confidence: 99%
“…The grain husbandry of Ukraine is a strategic and the most efficient branch of the national economy. Grain and products made from it have always been liquid, since they form the basis of the food base and security of the state (Andruszczak, 2017;Havryliuk & Krut, 2013). Unlike countries in Western Europe, Ukraine has the potential to develop and implement organic crop growing technologies over large areas.…”
Section: Introductionmentioning
confidence: 99%